The specifications of an expert system for configuring teleconferencing systems - Koushik, Geetha (Virginia Tech, 2014)
Use of teleconferencing systems can have a major impact on mobility-impaired office workers. This technology helps in bringing jobs to the workers' geographic 10catioIl, thereby integrating mobility-impaired workers into the work force. However, configuration of teleconferencing systems is difficult, time-consuming, and expensive. The aim of the work reported here was to find an affordaLle and efficient way of configuring teleconferencing systems. In the past, expert systems have been successful in solving similar configuration problems. In this report, an expert system is proposed to aid in the configuration of teleconferencing systems. The report also includes detailed problem specifications, justification for choosing an expert system as a solution, and high-level functional specifications for the development of an expert system. === Master of Science